The Influence of Virtual Try-On on Cosmetic Purchasing Decisions in the Shopee Application with Intervening Variable Purchase Interest - Pratama, Rahadian Aji; Hasanah, Retno Isni; Wibasuri, Anggalia (Proceeding International Conference on Information Technology and Business, 2023)
The cosmetics industry is an industry that can be said to have good growth and development in Indonesia. Shopping for cosmetics online also has problems, namely consumers cannot have experience in trying colors and textures compared to shopping directly in stores. The presence of the virtual try-on feature based on Augmented Reality (AR) technology provided by Shopee is the solution to this problem. This research aims to determine the effect of virtual try-on on cosmetic purchasing decisions on the Shopee application through purchase intention. The type of research used is quantitative causality research. The population selected in this research is consumers who have purchased cosmetic products on Shopee. The sampling method used in this research was nonprobability sampling using a purposive sampling technique, so 120 research samples were obtained. The data analysis method used in this research is Structural Equation Modeling using the Partial Least Square (PLS) method. The results of the analysis show that the test results show that the purchase interest variable is proven to have a positive and significant influence on cosmetic purchase decisions in the Shopee application. The virtual try-on variable is proven to have a positive and significant effect on cosmetic purchasing decisions on the Shopee application. The virtual try-on variable is proven to have a positive and significant effect on interest in buying cosmetics on the Shopee application. The virtual try-on variable influences the decision to purchase cosmetics in the Shopee application through purchase intention.Keywords— Virtual Try-On, Purchase Decision and Purchase Intention